Spontaneous nasal perforation in a bevacizumab‐treated patient with metastatic breast cancer. Issue 6 (27th August 2017) - Rodriguez, Cesar A.; Martin, Teresa; Lozano, Rebeca; Gomez, Amalia; Cruz, Juan J.
Abstract: Nasal septum perforation in patients with cancer receiving systemic therapy is rare, and its association with bevacizumab use has described recently in the literature. Here, we report the case of a 34‐year‐old woman with hormone‐sensitive, HER‐2/ neu negative, metastatic breast cancer who develope a nasal septum perforation during the treatment with paclitaxel and bevacizumab.